Hydroxyapatite-ferric oxide nanoparticle composite material and preparation method thereof

By coating hydroxyapatite particles on iron oxide nanoparticles and using magnetic attractions to each other to make them distributed in clusters, the problem of particles scattered in bone regeneration technology is solved, and the bone formation effect is improved.

CN119455138APending Publication Date: 2025-02-18成都医学院第一附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411616357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing guided bone regeneration technology, there is a lack of chemical and mechanical connection between the particles of bone grafting material, resulting in scattered distribution of particles, resulting in the loss of osteogenesis space and failure of osteogenesis.

Method used

Gelatin is used as a modification to coat iron oxide nanoparticles to form nanocomposite particles with core-shell structures. The mutual attraction between magnetic particles is used to make the particles cluster without dispersing and dispersing.

Benefits of technology

The stable clumping of hydroxyapatite particles is achieved, the effect of guiding bone regeneration is improved, and the problem of bone formation failure caused by scattered distribution of particles is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455138A_ABST
    Figure CN119455138A_ABST
Patent Text Reader

Abstract

The invention relates to a hydroxyapatite-ferric oxide nanoparticle composite material and a preparation method thereof. The composite material adopts iron oxide nanoparticles as a core, the surface layer is coated with a gelatin film, and a hydroxyapatite layer is taken as a shell, so that a core-shell structure is formed. The preparation process comprises the following six steps: firstly, preparing a gelatin buffer solution, and then respectively preparing a dipotassium hydrogen phosphate solution and a calcium chloride salt solution; uniformly dispersing the iron oxide nanoparticles in a gelatin buffer solution, and stirring in an ice-water bath to form gelatin-modified iron oxide nanoparticles I; stirring in a calcium chloride salt solution, and converting into ferric oxide nanoparticles II; and finally, adjusting the pH value in a dipotassium hydrogen phosphate solution, heating and stirring to form the hydroxyapatite-coated iron oxide nanoparticles. According to the method, hydroxyapatite particles can be effectively clustered through modification of gelatin, and the defect of particle dispersion in a traditional method is overcome, so that the osteogenesis effect is improved, and bone regeneration is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medical technology, and in particular relates to a hydroxyapatite-iron oxide nanoparticle composite material and a preparation method thereof. Background Art

[0002] Over the past two decades, oral implant technology has advanced by leaps and bounds, and dental implants have become one of the best restorative options for patients with missing teeth. However, clinically, thousands of patients still suffer from extensive bone defects each year due to various factors, such as severe trauma, severe infection, and maxillofacial tumors. Due to the difficulty of bone healing, poor bone quality, and insufficient bone quantity, these issues hinder implant placement, the initial stability, and long-term survival rate after implantation, significantly impacting patients' quality of life. This has become a clinical problem that needs to be urgently addressed in the oral implant restoration community.

[0003] Common methods for repairing alveolar bone defects include guided bone regeneration, block bone grafting, distraction osteogenesis, bone splitting, and many other techniques. Among them, guided bone regeneration is a relatively common bone augmentation method. Guided bone regeneration refers to the use of a biological barrier membrane to maintain the space created by surgery at the bone defect site, thereby blocking the ingress of rapidly proliferating epithelial cells and fibroblasts, and ensuring the growth of slower-proliferating osteoblasts and blood vessels. For the success of guided bone regeneration, four important key points must be noted: 1) the biological barrier membrane completely seals the defect area; 2) sufficient bone formation space is maintained under the biological barrier membrane; 3) the bone graft area maintains good stability; and 4) the bone graft bed should have good bone formation capacity.

[0004] Materials for guided bone regeneration are primarily composed of two components: a biological barrier membrane and a bone graft material. The types and characteristics of bone graft materials are as follows: 1. Autologous bone, such as the lateral chin plate, external oblique ridge of the mandible, external skull plate, and iliac bone, offers reliable osteogenesis, but bone availability is limited. 2. Allogeneic bone: Allogeneic bone is freeze-dried or decalcified, retaining bone matrix proteins and exhibiting a certain osteoinductive effect, but carries a risk of cross-infection. 3. Xenogeneic bone; 4. Heterogeneous bone: Inorganic, inert biomaterials, either synthetic or naturally occurring, such as hydroxyapatite and tricalcium phosphate.

[0005] In conventional guided bone regeneration techniques, bone graft material is placed in a granular form within the bone defect. The particles are not chemically or mechanically connected, resulting in a dispersed distribution. This often leads to bone migration, resulting in loss of bone formation space and ultimately bone formation failure. Some clinicians have mixed bone powder particles with plasma extracts—concentrated growth factors such as CGF and PRF—to form cohesive bone blocks. In these cohesive blocks, the bone powder aggregates in vitro and is then placed within the bone defect. However, because the plasma extract degrades in vivo over a short period of time, the bone powder returns to a dispersed state. Numerous studies have shown that the release of growth factors during the early stages of osteogenesis may play a role. However, at three or even six months, there is no significant difference in osteogenesis compared to the non-cohesive bone block group. This suggests the need for a more reliable method to stably connect the bone powder particles and prevent the loss of these connections during the early stages of osteogenesis.

[0006] Magnetic nanoparticles are a new material that has rapidly developed in recent years and has great potential for application in bone tissue engineering (magnetic materials such as γ-Fe2O3 and Fe3O4) and can promote osteogenesis and angiogenesis. Low-dose magnetic nanoparticles are safe and effective and are now approved by the FDA for the treatment of iron deficiency anemia. Studies have shown that when iron oxide nanoparticles are injected into the infarcted heart, magnetic guidance can reduce cell apoptosis and fibrosis, enhance angiogenesis, and promote cardiac function recovery.

[0007] There are two main approaches to surface modification of magnetic iron oxide nanoparticles: one is chemical bonding of the surface-modifying material to the particle surface, typically small organic molecules; the other is direct coating of the magnetic nanoparticles with organic or inorganic materials, primarily surfactants, polymers, precious metals, and silica. Surface modification not only enhances the stability of magnetic nanoparticles but also improves their dispersibility in aqueous solutions and biocompatibility, enhances targeting, prevents protein adsorption, and increases their circulation time. It also allows for further functionalization by incorporating other nanoparticles, compounds, or bioligands. Magnetic nanoparticles with an Fe₃O₄ core offer small diameters, high sensitivity, low toxicity, stable performance, and readily available raw materials. Fe₃O₄ generally has no toxic side effects on the human body, and the iron content of the carrier used during the entire treatment course does not exceed the standard iron supplementation requirement for anemia patients. While some of the iron is utilized by the body, the remaining magnetic particles can be safely excreted through the skin, bile, and kidneys. Surface modification with organic polymers or inorganic metals or oxides enhances their biocompatibility and makes them suitable for attaching bioactive molecules, thereby imparting functionality. Delivering drugs to specific sites can eliminate side effects and reduce drug dosages.

[0008] Therefore, this project proposes to use hydroxyapatite particles commonly used in guided bone regeneration, use gelatin as a modifier, and coat iron oxide nanoparticles to form nanocomposite particles. By utilizing the mutual attraction between magnetic particles, the hydroxyapatite particles with better osteogenesis effects can be clustered instead of being scattered. Summary of the Invention

[0009] In order to solve the above-mentioned defects in the prior art, the present invention provides a hydroxyapatite-iron oxide nanoparticle composite material and a preparation method thereof.

[0010] The technical solution adopted in the present invention is as follows:

[0011] A hydroxyapatite-iron oxide nanoparticle composite material comprises: the composite material is a core-shell structure material with iron oxide nanoparticles as the core, the surface of the iron oxide nanoparticles is coated with a gelatin film, and the hydroxyapatite layer covering the core is the shell.

[0012] Another aspect of the present invention provides a process for preparing a hydroxyapatite-iron oxide nanoparticle composite material, comprising the following steps:

[0013] S1: Prepare gelatin buffer solution with a tris(hydroxymethyl)aminomethane concentration of 8-10 mmol / L and a pH of 10-12;

[0014] S2: preparing a dipotassium hydrogen phosphate solution with a concentration of 0.2 to 1 mol / L;

[0015] S3: preparing a calcium chloride salt solution with a concentration of 0.2 to 1 mol / L;

[0016] S4: evenly dispersing the iron oxide nanoparticles in the gelatin buffer solution and stirring in an ice-water bath for 4 hours to form gelatin-modified iron oxide nanoparticles I;

[0017] S5: dispersing the iron oxide particles in a calcium chloride salt solution and stirring for 24 hours to form iron oxide nanoparticles II;

[0018] S6: Dispersing the iron oxide nanoparticles II in a dipotassium hydrogen phosphate solution, adjusting the pH to 11-13, and stirring at 70° C.-90° C. for 12-16 hours to form hydroxyapatite-coated iron oxide nanoparticles.

[0019] As a further preference, the step S1 is prepared using deionized water and tris(hydroxymethyl)aminomethane.

[0020] As a further preference, in steps S2 and S3, deionized water and the corresponding oxides are used to prepare a soluble salt solution.

[0021] As a further preferred embodiment, the step S4 specifically includes: uniformly dispersing the iron oxide nanoparticles in a gelatin buffer solution, stirring in an ice-water bath for 4 hours to coat the surface of the iron oxide nanoparticles with a uniform gelatin film, then standing for more than half an hour, separating the liquid phase, and rinsing and washing with a large amount of deionized water to obtain gelatin-modified iron oxide nanoparticles, which are recorded as iron oxide nanoparticles I.

[0022] As a further preferred embodiment, step S5 specifically includes: dispersing the iron oxide particles in a calcium chloride salt solution, wherein the amount of the calcium salt solution is sufficient to uniformly disperse the iron oxide nanoparticles therein, stirring for 24 hours to allow the gelatin to fully chelate with the calcium ions, and then standing for at least half an hour. After separating and removing the liquid phase, washing with deionized water until no precipitation is generated after adding the dipotassium hydrogen phosphate solution to the washed deionized water, to obtain iron oxide nanoparticles II.

[0023] As a further preferred embodiment, step S6 specifically includes: uniformly dispersing the iron oxide nanoparticles II in a dipotassium hydrogen phosphate solution, wherein the amount of the phosphate solution is sufficient to uniformly disperse the iron oxide nanoparticles II therein, and the molar ratio of the phosphate solution to the calcium salt solution in step S2 is approximately 0.65:1, adjusting the pH to 11-13 with aqueous ammonia, stirring the reaction at a temperature of 70°C to 90°C for at least 12 to 16 hours to coat the surface of the iron oxide nanoparticles II with a layer of hydroxyapatite, and then standing for at least half an hour to 1 hour, separating and removing the liquid phase, rinsing and washing with a large amount of deionized water, and vacuum drying to obtain a core-shell structure nanocomposite material of hydroxyapatite-coated iron oxide nanoparticles.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] In general, the hydroxyapatite-iron oxide nanoparticle composite material and preparation method provided by the present invention differ from the traditional method of preparing hydroxyapatite-coated silver nanoparticles in that the present method uses commonly used hydroxyapatite particles, uses gelatin as a modifier, and coats iron oxide nanoparticles to form nanocomposite particles. By utilizing the mutual attraction between magnetic particles, the hydroxyapatite particles with better osteogenesis effects can be clustered rather than dispersed, achieving the effect of clustering that is conducive to guiding bone regeneration, thereby solving the defect of the existing technology that causes the particles to be dispersed. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will now be described by way of example with reference to the accompanying drawings, in which:

[0027] Figure 1 Flowchart of the hydroxyapatite-iron oxide nanoparticle composite material and its preparation method in the present invention;

[0028] Figure 2 This is the microscopic morphology of the hydroxyapatite-iron oxide nanomaterial after 12 axes were immersed in simulated body fluid in the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The components of the embodiments of the present application generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.

[0030] This embodiment provides a hydroxyapatite-iron oxide nanoparticle composite material, which is a core-shell structure material with iron oxide nanoparticles as the core, the surface of the iron oxide nanoparticles coated with a gelatin film, and the hydroxyapatite layer covering the core as the shell.

[0031] Example 1

[0032] Another aspect of the present invention provides a process for preparing a hydroxyapatite-iron oxide nanoparticle composite material, comprising the following steps:

[0033] S1: Prepare gelatin buffer solution

[0034] Take tris (hydroxymethyl)aminomethane (Tris) powder and dissolve it in deionized water.

[0035] A Tris buffer solution with a concentration of 9 mmol / L was prepared and its pH was adjusted to 11 using a pH meter.

[0036] Add gelatin: Add appropriate amount of gelatin as needed and stir thoroughly until the gelatin is completely dissolved to ensure a uniform solution.

[0037] S2: Preparation of dipotassium hydrogen phosphate solution

[0038] Take potassium dihydrogen phosphate (K2HPO4) solid and dissolve it in deionized water.

[0039] Prepare a 0.6 mol / L dipotassium hydrogen phosphate solution and ensure that it is fully dissolved.

[0040] S3: Preparation of calcium chloride salt solution

[0041] Take calcium chloride (CaCl2) solid and dissolve it in deionized water.

[0042] Prepare a 0.5 mol / L calcium chloride salt solution and ensure that it is completely dissolved.

[0043] S4: Preparation of gelatin-modified iron oxide nanoparticles I

[0044] The iron oxide nanoparticles (Fe2O3 or Fe3O4) are uniformly dispersed in the gelatin buffer solution prepared in step S1.

[0045] The mixture was stirred in an ice-water bath for 4 hours to ensure that the surface of the iron oxide nanoparticles was evenly coated with a gelatin film.

[0046] After the mixture was allowed to stand for half an hour, the liquid phase was removed by centrifugation. After separation of the liquid phase, it was rinsed and washed with a large amount of deionized water to obtain gelatin-modified iron oxide nanoparticles, which were recorded as iron oxide nanoparticles I.

[0047] S5: Preparation of Iron Oxide Nanoparticles II

[0048] The iron oxide nanoparticles I are dispersed in the calcium chloride salt solution prepared in step S3 to ensure that the iron oxide particles are evenly dispersed.

[0049] Stir for 24 hours to allow gelatin to fully chelate with calcium ions.

[0050] The mixture was allowed to stand for at least half an hour, and after the liquid phase was separated, it was washed with deionized water until no precipitation was produced after adding dipotassium hydrogen phosphate solution to the washed deionized water, thereby obtaining iron oxide nanoparticles II.

[0051] S6: Preparation of Hydroxyapatite-Coated Iron Oxide Nanoparticles

[0052] The iron oxide nanoparticles II are uniformly dispersed in a dipotassium hydrogen phosphate solution, wherein the amount of the phosphate solution is sufficient to uniformly disperse the iron oxide nanoparticles II therein and the molar ratio of phosphorus to calcium in the phosphate solution to the calcium salt solution in step S2 is approximately 0.65:1; the pH is adjusted to 12 with aqueous ammonia, and the reaction is stirred at a temperature of 70° C. to 90° C. for at least 12 to 16 hours to coat the surface of the iron oxide nanoparticles II with a hydroxyapatite layer; the mixture is allowed to stand for at least half an hour to one hour, and after separating and removing the liquid phase, the mixture is rinsed and washed with a large amount of deionized water, and vacuum dried to obtain a core-shell structure nanocomposite material of hydroxyapatite-coated iron oxide nanoparticles.

[0053] Example 2

[0054] S1: Prepare gelatin buffer solution

[0055] Take tris (hydroxymethyl)aminomethane (Tris) powder and dissolve it in deionized water.

[0056] A Tris buffer solution with a concentration of 8 mmol / L was prepared and its pH was adjusted to 12 using a pH meter.

[0057] Add gelatin: Add appropriate amount of gelatin as needed and stir thoroughly until the gelatin is completely dissolved to ensure a uniform solution.

[0058] S2: Preparation of dipotassium hydrogen phosphate solution

[0059] Take potassium dihydrogen phosphate (K2HPO4) solid and dissolve it in deionized water.

[0060] Prepare a 0.2 mol / L dipotassium hydrogen phosphate solution and ensure that it is fully dissolved.

[0061] S3: Preparation of calcium chloride salt solution

[0062] Take calcium chloride (CaCl2) solid and dissolve it in deionized water.

[0063] Prepare a 0.2 mol / L calcium chloride salt solution and ensure that it is completely dissolved.

[0064] S4: Preparation of gelatin-modified iron oxide nanoparticles I

[0065] The iron oxide nanoparticles (Fe2O3 or Fe3O4) are uniformly dispersed in the gelatin buffer solution prepared in step S1.

[0066] The mixture was stirred in an ice-water bath for 4 hours to ensure that the surface of the iron oxide nanoparticles was evenly coated with a gelatin film.

[0067] After the mixture was allowed to stand for half an hour, the liquid phase was removed by centrifugation. After separation of the liquid phase, it was rinsed and washed with a large amount of deionized water to obtain gelatin-modified iron oxide nanoparticles, which were recorded as iron oxide nanoparticles I.

[0068] S5: Preparation of Iron Oxide Nanoparticles II

[0069] The iron oxide nanoparticles I are dispersed in the calcium chloride salt solution prepared in step S3 to ensure that the iron oxide particles are evenly dispersed.

[0070] Stir for 24 hours to allow gelatin to fully chelate with calcium ions.

[0071] The mixture was allowed to stand for at least half an hour, and after the liquid phase was separated, it was washed with deionized water until no precipitation was produced after adding dipotassium hydrogen phosphate solution to the washed deionized water, thereby obtaining iron oxide nanoparticles II.

[0072] S6: Preparation of Hydroxyapatite-Coated Iron Oxide Nanoparticles

[0073] The iron oxide nanoparticles II are uniformly dispersed in a dipotassium hydrogen phosphate solution, wherein the amount of the phosphate solution is sufficient to uniformly disperse the iron oxide nanoparticles II therein and the molar ratio of phosphorus to calcium in the phosphate solution to the calcium salt solution in step S2 is approximately 0.65:1; the pH is adjusted to 11 with aqueous ammonia, and the reaction is stirred at a temperature of 70° C. to 90° C. for at least 12 to 16 hours to coat the surface of the iron oxide nanoparticles II with a hydroxyapatite layer; the mixture is allowed to stand for at least half an hour to one hour, and after separating and removing the liquid phase, the mixture is rinsed and washed with a large amount of deionized water, and vacuum dried to obtain a core-shell structure nanocomposite material of hydroxyapatite-coated iron oxide nanoparticles.

[0074] Example 3

[0075] S1: Prepare gelatin buffer solution

[0076] Take tris (hydroxymethyl)aminomethane (Tris) powder and dissolve it in deionized water.

[0077] A Tris buffer solution with a concentration of 10 mmol / L was prepared and its pH was adjusted to 10 using a pH meter.

[0078] Add gelatin: Add appropriate amount of gelatin as needed and stir thoroughly until the gelatin is completely dissolved to ensure a uniform solution.

[0079] S2: Preparation of dipotassium hydrogen phosphate solution

[0080] Take potassium dihydrogen phosphate (K2HPO4) solid and dissolve it in deionized water.

[0081] Prepare a 1 mol / L dipotassium hydrogen phosphate solution and ensure that it is fully dissolved.

[0082] S3: Preparation of calcium chloride salt solution

[0083] Take calcium chloride (CaCl2) solid and dissolve it in deionized water.

[0084] Prepare a 1 mol / L calcium chloride salt solution and ensure that it is completely dissolved.

[0085] S4: Preparation of gelatin-modified iron oxide nanoparticles I

[0086] The iron oxide nanoparticles (Fe2O3 or Fe3O4) are uniformly dispersed in the gelatin buffer solution prepared in step S1.

[0087] The mixture was stirred in an ice-water bath for 4 hours to ensure that the surface of the iron oxide nanoparticles was evenly coated with a gelatin film.

[0088] After the mixture was allowed to stand for half an hour, the liquid phase was removed by centrifugation. After separation of the liquid phase, it was rinsed and washed with a large amount of deionized water to obtain gelatin-modified iron oxide nanoparticles, which were recorded as iron oxide nanoparticles I.

[0089] S5: Preparation of Iron Oxide Nanoparticles II

[0090] The iron oxide nanoparticles I are dispersed in the calcium chloride salt solution prepared in step S3 to ensure that the iron oxide particles are evenly dispersed.

[0091] Stir for 24 hours to allow gelatin to fully chelate with calcium ions.

[0092] The mixture was allowed to stand for at least half an hour, and after the liquid phase was separated, it was washed with deionized water until no precipitation was produced after adding dipotassium hydrogen phosphate solution to the washed deionized water, thereby obtaining iron oxide nanoparticles II.

[0093] S6: Preparation of Hydroxyapatite-Coated Iron Oxide Nanoparticles

[0094] The iron oxide nanoparticles II are uniformly dispersed in a dipotassium hydrogen phosphate solution, wherein the amount of the phosphate solution is sufficient to uniformly disperse the iron oxide nanoparticles II therein and the molar ratio of phosphorus to calcium in the phosphate solution to the calcium salt solution in step S2 is approximately 0.65:1; the pH is adjusted to 13 with aqueous ammonia, and the reaction is stirred at a temperature of 70° C. to 90° C. for at least 12 to 16 hours to coat the surface of the iron oxide nanoparticles II with a hydroxyapatite layer; the mixture is allowed to stand for at least half an hour to one hour, and after separating and removing the liquid phase, the mixture is rinsed and washed with a large amount of deionized water, and vacuum dried to obtain a core-shell structure nanocomposite material of hydroxyapatite-coated iron oxide nanoparticles.

[0095] Characterize the composite material of any of the above examples

[0096] The purpose is to test the performance of hydroxyapatite (HA)-coated iron oxide (Fe2O3) nanoparticles, mainly including morphology, structural composition, biomechanical properties and degradation characteristics. The following are the specific test plans and steps:

[0097] 1. Morphology and structure detection

[0098] Surface and internal morphology observation:

[0099] Scanning electron microscopy (SEM) was used to observe the surface and internal morphology of the bone graft material and analyze the distribution, shape and size of the particles.

[0100] Transmission electron microscopy (TEM) was used to further investigate the internal structure and crystal morphology of the nanoparticles.

[0101] Structural component analysis:

[0102] X-ray diffraction (XRD) was used to detect the crystal phase composition of hydroxyapatite and iron oxide.

[0103] The chemical composition and functional groups of the materials were analyzed by Fourier transform infrared spectroscopy (FTIR).

[0104] 2. Biomechanical performance testing

[0105] Universal learning instrument detection:

[0106] The mechanical properties of bone graft materials were tested using a universal mechanical instrument, including compressive strength, tensile strength, and flexural strength, to evaluate their applicability in biological environments.

[0107] 3. Stability testing

[0108] Hydroxyapatite-iron oxide nanoparticles aggregation stability test:

[0109] Dynamic light scattering (DLS) was used to examine the particle size distribution and aggregation state of the particles and to evaluate their stability in biological applications.

[0110] 4. In vitro degradation studies

[0111] Simulated body fluid immersion experiment:

[0112] The hydroxyapatite-iron oxide nanomaterials were immersed in simulated body fluid.

[0113] Take samples regularly and use SEM to observe the micromorphological changes of the material. Figure 2 This is a diagram showing the surface micromorphology of the multiphase membrane formed after 12 weeks, analyzing the changes in surface roughness during the degradation process.

[0114] The degradation rate is determined by mass change, and the mass and volume changes of the substance before and after degradation are recorded.

[0115] 5. Data Analysis

[0116] All experimental results were statistically analyzed to compare the changes in morphology, structure and mechanical properties at different time points, and to evaluate the biocompatibility and potential application value of the materials.

[0117] Through the above steps, the performance of hydroxyapatite-coated iron oxide nanoparticles can be comprehensively evaluated, providing a scientific basis for their application in the biomedical field.

[0118] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features thereof can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hydroxyapatite-iron oxide nanoparticle composite material, characterized in that: include: The composite material is a core-shell structure material with iron oxide nanoparticles as the core, the surface of the iron oxide nanoparticles covered with a gelatin film, and the hydroxyapatite layer covering the core as the shell.

2. The hydroxyapatite-coated iron oxide nanoparticles according to claim 1, characterized in that: The following steps are involved: S1: prepare gelatin buffer solution, the concentration of tris(hydroxymethyl)aminomethane is 8-10mmol / L, and the pH is 10-12; S2: preparing a dipotassium hydrogen phosphate solution with a concentration of 0.2 to 1 mol / L; S3: preparing a calcium chloride salt solution with a concentration of 0.2 to 1 mol / L; S4: uniformly dispersing the iron oxide nanoparticles in the gelatin buffer solution, stirring in an ice water bath for 4 hours, to form gelatin-modified iron oxide nanoparticles I; S5: dispersing the iron oxide particles in a calcium chloride salt solution and stirring for 24 hours to form iron oxide nanoparticles II; S6: Dispersing the iron oxide nanoparticles II in a dipotassium hydrogen phosphate solution, adjusting the pH to 11-13, and stirring at 70° C.-90° C. for 12-16 hours to form hydroxyapatite-coated iron oxide nanoparticles.

3. The hydroxyapatite-coated iron oxide nanoparticles according to claim 2, characterized in that: In the step S1, deionized water and tris(hydroxymethyl)aminomethane are used to prepare the mixture.

4. The hydroxyapatite-coated iron oxide nanoparticles according to claim 2, characterized in that: In the steps S2 and S3, deionized water and corresponding oxides are used to prepare a soluble salt solution.

5. The hydroxyapatite-coated iron oxide nanoparticles according to claim 2, characterized in that: The step S4 specifically includes: uniformly dispersing the iron oxide nanoparticles in the gelatin buffer solution, stirring in an ice water bath for 4 hours to coat the surface of the iron oxide nanoparticles with a uniform gelatin film, and then standing for more than half an hour. After separating the liquid phase, rinsing and washing with a large amount of deionized water to obtain gelatin-modified iron oxide nanoparticles, which are recorded as iron oxide nanoparticles I.

6. The hydroxyapatite-coated iron oxide nanoparticles according to claim 2, characterized in that: The step S5 specifically comprises: dispersing the iron oxide particles in a calcium chloride salt solution, wherein the amount of the calcium salt solution is sufficient to uniformly disperse the iron oxide nanoparticles therein, stirring for 24 hours to allow gelatin to fully chelate with calcium ions, and then standing for at least half an hour, separating and removing the liquid phase, and washing with deionized water until no precipitation is produced after adding the potassium hydrogen phosphate solution to the washed deionized water, thereby obtaining iron oxide nanoparticles II.

7. A hydroxyapatite-iron oxide nanoparticle composite material and a preparation method thereof according to claim 2, characterized in that: The step S6 specifically comprises: uniformly dispersing the iron oxide nanoparticles II in a dipotassium hydrogen phosphate solution, wherein the amount of the phosphate solution is sufficient to uniformly disperse the iron oxide nanoparticles II therein, and the molar ratio of the phosphate solution to the calcium salt solution in step S2 is about 0.65:1, adjusting the pH to 11-13 with aqueous ammonia, stirring the reaction at a temperature of 70° C. to 90° C. for at least 12-16 hours to coat the surface of the iron oxide nanoparticles II with a layer of hydroxyapatite, then standing for at least half an hour to one hour, separating and removing the liquid phase, rinsing and washing with a large amount of deionized water, and vacuum drying to obtain a core-shell structure nanocomposite material of hydroxyapatite-coated iron oxide nanoparticles.